Murder on the orient express eaudiobook - Christie, Agatha (Hercule Poirot, 2017)
A new recording of the most widely read mystery of all time, performed by Kenneth Branagh. Now a major motion picture from Twentieth Century Fox, releasing November 10, 2017 and directed by Kenneth Branagh. "The murderer is with us - on the train now..." Just after midnight, the famous Orient Express is stopped in its tracks by a snowdrift. By morning, the millionaire Samuel Edward Ratchett lies dead in his compartment, stabbed a dozen times, his door locked from the inside. One of his fellow passengers must be the murderer. "What more . . . can a mystery addict desire?"—New York Times